1993
DOI: 10.1093/infdis/167.4.789
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Intake Increases Human Immunodeficiency Virus Type 1 Replication in Human Peripheral Blood Mononuclear Cells

Abstract: The effects of alcohol consumption on various T lymphocyte subset functions and on the degree of susceptibility of peripheral blood mononuclear cells (PBMC) to human immunodeficiency virus (HIV) type 1 infection and replication in vitro were investigated. PBMC from 60 HIV-1-seronegative healthy volunteers were studied before and after ingestion of alcohol beverages. After alcohol consumption, there was significantly increased HIV-1 replication (P < .001) in PBMC, as determined by HIV-1 p24 antigen levels in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 32 publications
1
56
0
Order By: Relevance
“…[32][33][34][35][36] Our study showed significantly higher levels of HIV-1 p24 in the plasma of hu-PBL-NOD/ SCID HIVE mice chronically exposed to ethanol as compared to controls fed an isocaloric diet (Table 2). Although the effects of ethanol on HIV-1 infection still remain inconclusive, our results parallel observations in which chronic alcohol exposure in macaques infected with simian immunodeficiency virus (animal model for HIV-1 infection) resulted in high plasma viral load.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35][36] Our study showed significantly higher levels of HIV-1 p24 in the plasma of hu-PBL-NOD/ SCID HIVE mice chronically exposed to ethanol as compared to controls fed an isocaloric diet (Table 2). Although the effects of ethanol on HIV-1 infection still remain inconclusive, our results parallel observations in which chronic alcohol exposure in macaques infected with simian immunodeficiency virus (animal model for HIV-1 infection) resulted in high plasma viral load.…”
Section: Discussionmentioning
confidence: 99%
“…For example, alcohol intake has been shown to increase human immunodeficiency virus replication in human peripheral blood mononuclear cells in culture. 13 The T lymphocyte system seems to be extensively affected by alcohol. There might be a transient immunosuppressive environment in which viruses (HIV and, possibly, HCV) replicate faster than in intact immune sytem.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12] Moreover relations between alcohol and the immune response have been suggested with other viral infections. 13 The aim of the present study is to describe the effect of moderate alcohol intake on serum HCV RNA levels and histological liver lesions in patients with chronic HCV infection. …”
mentioning
confidence: 99%
“…Suppressed T-cell proliferation caused by retrovirus infection was significantly reduced further by dietary alcohol [195]. Although alcohol had no effect on the relative production of CD4 þ and CD8 þ lymphocytes, reductions of lymphocyte-produced IL-2 and of the soluble immune response activity of suppressor cells occurred [196]. Alcohol consumption suppresses IFN-production by human peripheral blood lymphocytes [197] and antiviral CD8 þ T cells [128].…”
Section: Alcohol and Innate Immunitymentioning
confidence: 99%